Insights on mining the pangenome of Sphingobacterium thalpophilum NMS02 S296 from the resistant banana cultivar Pisang lilin confirms the antifungal action against Fusarium oxysporum f. sp. cubense - Ajesh, B. R.; Sariga, R.; Nakkeeran, S.; Renukadevi, P.; Saranya, N.; Alkahtani, Saad (Frontiers in Microbiology, 2024)
Fusarium wilt, incited by Fusarium oxysporum f. sp. cubense (Foc), is a significant global threat in banana cultivation. Conventional disease management methods face increasing challenges, necessitating alternative strategies. Bacterial endophytes from resistant genotypes have gained attention for their potential as biocontrol agents due to their ability to suppress plant pathogens through various mechanisms. Sphingobacterium thalpophilum, a bacterial endophyte isolated from the resistant banana cultivar Pisang lilin (JALHSB010000001-JALHSB010000029), presents an intriguing prospect for combating Fusarium wilt. However, its underlying biocontrol mechanisms remain poorly understood. This study aimed to elucidate the antifungal efficacy of S. thalpophilum NMS02 S296 against Foc and explore the underlying mechanisms at the genomic level. The primary objective was to demonstrate the biocontrol potential of this bacterial endophyte, unravel the genetic basis for its antifungal activity through whole genome sequencing, and validate the findings. Sphingobacterium thalpophilum NMS02 S296 was subjected to whole genome sequencing using next-generation sequencing technologies and bioinformatics analyses to identify genes associated with antifungal properties. In vitro assays were conducted to assess the inhibitory effect of the bacterial isolate on the mycelial growth of Fusarium oxysporum f. sp. cubense. To explore the biomolecules responsible for the observed antagonistic activity, metabolites diffused into the agar at the zone of inhibition between Foc S16 and S. thalpophilum NMS02 S296 were extracted and identified. The whole genome sequencing of S. thalpophilum NMS02 S296 revealed an array of genes encoding antifungal enzymes and secondary metabolites. In vitro experiments demonstrated significant inhibition of the mycelial growth of Foc by the bacterial endophyte. Comparative genomic analysis highlighted the unique genomic features in S. thalpophilum associated with its biocontrol potential, setting it apart from other bacterial species. Our findings underscore the remarkable antifungal efficacy of S. thalpophilum NMS02 S296 against Fusarium wilt. The whole genome sequencing approach unveiled the genetic basis for its biocontrol potential, shedding light on the mechanisms underlying its antifungal activity. This study advances our understanding of bacterial endophytes as biocontrol agents and offers a promising avenue for plant growth promotion towards sustainable strategies to mitigate Fusarium wilt in banana cultivation.